Sequential two-step, one-pot microwave-assisted Urech synthesis of 5-monosubstituted hydantoins from L-amino acids in water - Chang, Wei-Jin; Liew, Sook Yee; Kurz, Thomas; Tan, Siow-Ping (Beilstein Journal of Organic Chemistry, 2025)
The hydantoin scaffold is renowned for its wide-ranging biological activities, including antibacterial, antiviral, anticancer, anti-inflammatory, and anticonvulsant effects. In this study, we present an innovative, sustainable approach to synthesizing hydantoins (H2a–j) directly from amino acids. This method employs a column chromatography-free, two-step, one-pot microwave-assisted synthesis that delivers hydantoins in yields ranging from 34% to 89%. The protocol demonstrates exceptional functional group tolerance, accommodating phenyl, aliphatic, phenol, alcohol, heterocyclic, and sulfide groups. This scalable, rapid, and eco-friendly strategy offers a promising avenue for the efficient synthesis of hydantoins, aligning with green chemistry principles and expanding the accessibility of these bioactive compounds for pharmaceutical applications.
Keywords: amino acids; hydantoin; microwave-assisted; one-pot reaction; Urech synthesis